This simplifies to -9 + 16x + 36.
So the expression becomes 16x + 27.
implify the expression by using the distrubutive property and combining like terms:
-9 + 4(4x + 9)
(1 point)
Responses

32x + 16
32x + 16

16x
16x

27 + 16x
27 + 16x

16x + 18
5 answers
this isnt one of the answers
Apologies for the oversight in my previous response. Let's simplify the expression correctly this time:
-9 + 4(4x + 9) =
-9 + 16x + 36 =
16x + 27
Therefore, the correct simplified expression is 16x + 27.
-9 + 4(4x + 9) =
-9 + 16x + 36 =
16x + 27
Therefore, the correct simplified expression is 16x + 27.
are you sure
Let's simplify the expression correctly:
-9 + 4(4x + 9) = -9 + 16x + 36 = 16x + 27
Therefore, the simplified expression is 16x + 27. Thank you for your patience.
-9 + 4(4x + 9) = -9 + 16x + 36 = 16x + 27
Therefore, the simplified expression is 16x + 27. Thank you for your patience.